UTILIZATION OF RAPESEED MEAL/CAKE IN POULTRY FEED. III. EFFECT OF INCORPORATING INCREASED LEVELS OF RAPESEED CAKE «PoST-AuTOCLAVING EXTRACTION) ON PERFORMANCE OF BROWN-EGG-LAYER (TETRA SL). (Biological Sciences - PJSIR, 2001)
The effect of increased levels of rapeseed cake obtained from autoclaved rapeseed on laying performance of brown-egg- layer was studied. The rapeseed cake (RSC) remaining after extraction of oil from the seed, was incorporated 111 layer ration at levels of 15, 20 and 25%. The birds fed on RSC diet were observed for production performance, feed intake and feed conversion ratio, liveability and egg quality parameters and then compared with birds maintained on standard ratron (RSC free diet). The results indicated higher egg production in standard and 15% RSC group (61 and 60% respectively), though statistically nonsignificant, compared to the other two group (55% each). Egg size slightly decreased from 63.26~ (standard group) to 59.17g (25% RSC group). Increase in the level of RSC resulted 111 increase m the prop_~rtJonof ego white and decrease in yolk of hens red on it. Similarly, the protem content of egg white of hen receiving 2) Yo RSC was maximum and its yolk protein content was minimum, indicating some influence of RSC. on protem biosynthesis, Organo- leptic tests judge by 7 experienced persons revealed no difference in overall acceptability among different groups.